Comparison of the anaesthetic efficacy of epinephrine concentrations (1 : 80 000 and 1 : 200 000) in 2% lidocaine for inferior alveolar nerve block in patients with symptomatic irreversible pulpitis: a randomized, double‐blind clinical trial. (29th July 2013) - Aggarwal, V.; Singla, M.; Miglani, S.; Kohli, S.
Abstract Aim The aim of this randomized controlled, double‐blind trial was to comparatively evaluate the anaesthetic efficacy and injection pain of 1.8 mL of 2% lidocaine with different concentrations of epinephrine (1 : 80 000 and 1 : 200 000) in patients with symptomatic irreversible pulpitis. Methodology Sixty‐two adult volunteers, actively experiencing pain, were randomly allocated into 2 groups and received 1.8 mL of 2% lidocaine with either 1 : 80 000 or 1 : 200 000 epinephrine concentration. Endodontic access preparation was initiated 15 min after the initial IANB. Pain during treatment was recorded using the Heft‐Parker visual analogue scale (HP VAS). The primary outcome measure, and the definition of 'success', was the ability to undertake pulp access and canal instrumentation with no or mild pain (HP VAS score <55 mm). Secondary outcome measure was the pain experienced during LA solution deposition. Statistical analysis was performed using Mann–Whitney U‐test and chi‐square test. Results The anaesthetic success rates of 2% lidocaine solutions containing 1 : 80 000 and 1 : 200 000 epinephrine concentrations were 20% and 28%, respectively. The difference was not statistically significant. There was also no significant difference in the pain experienced during deposition of the solutions. Conclusions Two percent lidocaine solution used for IANB achieved similar success rates when used with 1 : 80 000 or 1 : 200 000 epinephrine concentration.